Inter-annual and seasonal trends in cetacean distribution, density and abundance off southern California - Campbell, G.S.; Thomas, L.; Whitaker, K.; Douglas, A.B.; Calambokidis, J.; Hildebrand, J.A. (Deep Sea Research Part II: Topical Studies in Oceanography, 2015)
Funding was provided by the Chief of Naval Operations Environmental Readiness Division, the United States Navy’s Pacific Fleet, the Naval Postgraduate School Grant #N00244-11-1-027, and the Naval Facilities Engineering Command Living Marine Resources Program. Trends in cetacean density and distribution off southern California were assessed through visual line-transect surveys during thirty-seven California Cooperative Oceanic Fisheries Investigations (CalCOFI) cruises from July 2004–November 2013. From sightings of the six most commonly encountered cetacean species, seasonal, annual and overall density estimates were calculated. Blue whales (Balaenoptera musculus), fin whales (Balaenoptera physalus) and humpback whales (Megaptera novaeangliae) were the most frequently sighted baleen whales with overall densities of 0.91/1000 km2 (CV=0.27), 2.73/1000 km2 (CV=0.19), and 1.17/1000 km2 (CV=0.21) respectively. Species specific density estimates, stratified by cruise, were analyzed using a generalized additive model to estimate long-term trends and correct for seasonal imbalances. Variances were estimated using a non-parametric bootstrap with one day of effort as the sampling unit. Blue whales were primarily observed during summer and fall while fin and humpback whales were observed year-round with peaks in density during summer and spring respectively. Short-beaked common dolphins (Delphinus delphis), Pacific white-sided dolphins (Lagenorhynchus obliquidens) and Dall’s porpoise (Phocoenoidesdalli) were the most frequently encountered small cetaceans with overall densities of 705.83/1000 km2 (CV=0.22), 51.98/1000 km2 (CV=0.27), and 21.37/1000 km2 (CV=0.19) respectively. Seasonally, short-beaked common dolphins were most abundant in winter whereas Pacific white-sided dolphins and Dall’s porpoise were most abundant during spring. There were no significant long-term changes in blue whale, fin whale, humpback whale, short-beaked common dolphin or Dall’s porpoise densities while Pacific white-sided dolphins exhibited a ...